On some lesser known sea cucumbers in the Natural History Museum, UK (Echinodermata: Holothuroidea) - Thandar, Ahmed S. (Zootaxa, 2019)
A mixed batch of sea cucumbers tentatively labelled as ?Thyone or ?Havelockia species was obtained on loan from the Natural History Museum, United Kingdom (NHMUK) for identifications and records. The material dates back to 1850 and originates from shallow waters from various parts of the world. The material includes two new species and one new subspecies which have already been described in an earlier paper (see Thandar, 2017). The remaining specimens comprise a few known or poorly known nominal species and several indeterminate forms. This paper describes the known species while adding some useful information about them. Of the indeterminate species included are several specimens most belonging to the genus Thyone or Havelockia which, because of their incompleteness and absence of ossicles, are not identified beyond their suspected genus or species.